(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2020)
The aim of this study was to identify the chemical constituents of Elaeis guineensis (EG) using GCMS. EG fruits were purchased from a local market in Edo state and was identified, cleaned, boiled and extracted. The resultant crude extract was strained through filter paper and partitioned into n-hexane, dichloromethane and ethyl acetate before subjected to GC-MS analysis. Eighty-two (82) compounds were identified and the major components are hexadecanoic acid, methyl ester (10.53%), oleic acid (25.92%). n-hexadecanoic acid (31.41%), cis-vaccenic acid (22.82%) and octadecanoic acid (13.16%). Plants fatty acids are important for growth and defence mechanism against pathogen, possess antimicrobial action, implicated in pathway elucidation and stimulation of resistance mechanism in plants. Long chain fatty acids exert their effect on membrane phospholipids by modifying its composition and potentially interfering with synthesis of lipid signalling molecules. Identification of EG fruits have provided an idea of its chemical composition of the extract of E. guineensis. Dhaka Univ. J. Pharm. Sci. 19(2): 153-159, 2020 (December)